Russian Business Medium: Competition Problems - Sadriev, Ruslan D.; Mullakhmetov, Khanif S.; Akhmetshin, Elvir M. (International Journal of Economics and Financial Issues, 2016)
The research purpose is the system analysis of the business medium in Russia, its main characteristics and features detection that, according to the authors, will allow to adapt the existing approaches to management of the companies competitiveness to the Russian realities taking into account the revealed restrictions. During the research, it was revealed that in the Russian business medium the forces of the non-market character, finally leading to competition distortion, have the considerable impact on the companies. In the study, the competition distortion is presented as the sophisticated multidimensional phenomenon requiring the complex study. In article, the short review of the competitiveness assessment existing methods is made and the application need of the companies’ competitiveness assessment method, constructed on the analysis of the wide range of factors that define the business specifics in the Russian reality, is proved. The competition-expanded understanding based on the institutional approach is offered. The next step in the development of the proposed approach is the allocation of such phenomenon as the competition distortion and its separate study. Proceeding from the institutional approach the competition distortion is considered in three planes: the economy - the economic rules distortion, the state system - the constitutional rules distortion, the society - the distortion above- constitutional rules. A large number of different manifestations of the competition distortions in the Russian business medium was revealed. The competition distortion reasons are defined, the competition distortion influence to the companies’ management organization is examined. Keywords: the business medium, competitiveness, the competitiveness assessment method, the competition distortion, the institutional environment JEL Classifications: D23, L22, F12